Anthropometry of the nose: a comparative study between adult male Santhals and Bengalis in Bangladesh - Shah, MRI; Anwar, S; Mondal, DK; Yesmin, S; Ahmed, S (Mediscope, 2015)
Anthropometry is a scientific methods for taking various measurements of body parts and observation on the living subjects, which play an important role in distinguishing a pure race. The nose is a person's most defining feature because it is at the center of the face. The shape of the nose is a signature indicating the ethnicity, race, age and sex. The aim of this study is to document the mean nasal length, nasal width and nasal index of adult male Santhals and Bengalis in Bangladesh, which provides a comprehensive data for comparisons between each other and with the other ethnic group. Santhals, our study subjects living in the northwest part of Bangladesh, are usually recognized as an ethnic community. Because the Santhals have separate identity and their physical appearance is distinctive to some extent. The study, descriptive, observational and cross sectional is nature, was carried out in the Department of Anatomy, Rangpur Medical College, Rangpur, during the season of July, 2011 to June, 2012. A total number of 100 adult male Santhals and 100 adult male Bengalis were included from different location of Rangur and Dinajpur districts. Nasal length and nasal width were measured using sliding caliper and nasal index was calculated. Unpaired t-test was used to compare the measurement. The mean nose length of the Bengalis were significantly higher than the Santhals but the mean of nose width were significantly higher in Santhals than Bengalis. Most of the Santhals were mesorrhine, but most of the Bengalis were leptorrhine. Mediscope Vol. 2, No. 2: July 2015, Pages 28-32